2017
DOI: 10.5391/ijfis.2017.17.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Plant Leaf Recognition Using a Convolution Neural Network

Abstract: There are hundreds of kinds of trees in the natural ecosystem, and it can be very difficult to distinguish between them. Botanists and those who study plants however, are able to identify the type of tree at a glance by using the characteristics of the leaf. Machine learning is used to automatically classify leaf types. Studied extensively in 2012, this is a rapidly growing field based on deep learning. Deep learning is itself a self-learning technique used on large amounts of data, and recent developments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(48 citation statements)
references
References 8 publications
0
46
0
2
Order By: Relevance
“…For further analysis of the performance of DMS-Robust Alexnet, a comparison is performed with GA-SVM [51], SEG-KNN [20], SIMPLE-CNN [33], VGGNet [40], GoogleNet [52] and ResNet [53], maize disease recognition baselines. The comparison results are indicated in Table 7.…”
Section: ) Comparison With Baseline Methodsmentioning
confidence: 99%
“…For further analysis of the performance of DMS-Robust Alexnet, a comparison is performed with GA-SVM [51], SEG-KNN [20], SIMPLE-CNN [33], VGGNet [40], GoogleNet [52] and ResNet [53], maize disease recognition baselines. The comparison results are indicated in Table 7.…”
Section: ) Comparison With Baseline Methodsmentioning
confidence: 99%
“…Liu et al used convolutional neural network (CNN) for analyzing hyperspectral data, and their results indicated that the deep learning framework can give excellent performance for detection of defect regions on surface-defective cucumbers [ 21 ]. Jeon and Rhee also used CNN model to classify leaves, and the recognition rate was greater than 94% [ 22 ]. Similar CNN models were also used for tomato disease recognition [ 23 ] and melon lesion detection [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A deep convolution neural network (DCNN) is a multilayer neural network that is performed as a deep supervised learning method [15]. The DCNN has achieved excellent performances on image recognition tasks for the last few years [7,8,16,17]. It can perform both feature extraction and image classification tasks [15].…”
Section: Dcnn Classifiermentioning
confidence: 99%